2007
DOI: 10.1111/j.1365-2400.2007.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Movements by wild brown trout in a boreal river: response to habitat and flow contrasts

Abstract: Radio transmitters were implanted in wild brown trout, Salmo trutta L., in the River Ma˚na at low summer water flows (n = 18), higher flow in summer (n = 20), and variable, peaking flows in autumn (n = 20), and tracked two to four times day and night for 4-5 weeks. Individuals were caught and released in a 4-km uniformly channelised section, and in a 4-km natural diverse river section. Substantial individual variation in home range and total movement (924-85 818 m 2 and 295-7014 m) suggested flexibility to ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…The movement rates we observed were also similar to the range of movement rates reported for spawning rainbow trout Oncorhynchus mykiss in New Zealand (321-487 m/d; Dedual and Jowett 1999;Venman and Dedual 2005), but lower than that reported for bull trout Salvelinus confluentus (up to 4.4 km/d; Swanberg 1997). The total distances moved by brown trout in our study (up to 41 km) were also within the range reported elsewhere for brown trout (Allen 1951;Clapp et al 1990;Meyers et al 1992;Burrell et al 2000;Knouft and Spotila 2002;Ovidio et al 2002;Bettinger and Bettoli 2004;Diana et al 2004;Rustadbakken et al 2004;Heggenes et al 2007), although somewhat less than the 76-202 km reported by Young (1994), Wilson and Boubee (1996), and Strickland et al (1999). Maximum movements are presumably constrained by the size of the catchments studied and the distances among foraging, refuge and spawning habitats.…”
Section: Rates Of Movementsupporting
confidence: 62%
See 2 more Smart Citations
“…The movement rates we observed were also similar to the range of movement rates reported for spawning rainbow trout Oncorhynchus mykiss in New Zealand (321-487 m/d; Dedual and Jowett 1999;Venman and Dedual 2005), but lower than that reported for bull trout Salvelinus confluentus (up to 4.4 km/d; Swanberg 1997). The total distances moved by brown trout in our study (up to 41 km) were also within the range reported elsewhere for brown trout (Allen 1951;Clapp et al 1990;Meyers et al 1992;Burrell et al 2000;Knouft and Spotila 2002;Ovidio et al 2002;Bettinger and Bettoli 2004;Diana et al 2004;Rustadbakken et al 2004;Heggenes et al 2007), although somewhat less than the 76-202 km reported by Young (1994), Wilson and Boubee (1996), and Strickland et al (1999). Maximum movements are presumably constrained by the size of the catchments studied and the distances among foraging, refuge and spawning habitats.…”
Section: Rates Of Movementsupporting
confidence: 62%
“…Research on river-resident salmonids over the last 15 years has indicated that widespread movement is much more common than previously thought (Gowan et al 1994;Young 1996;Young et al 1997;Diana et al 2004;Mellina et al 2005;Heggenes et al 2007). Movement can be within an extended home range of several hundred meters (Rodriguez 2002;Diana et al 2004;Mellina et al 2005;Roghair 2005) up to largerscale movements of many kilometers (Clapp et al 1990;Bettinger and Bettoli 2004;Gresswell and Hendricks 2007;Heggenes et al 2007).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous field studies found no consistent effect of sudden, extreme peaking flows (ranging from 0.15 to [200 m 3 s -1 ) on area use or movements by adult trout and salmon (Bunt et al 1999;Gido et al 2000;Heggenes et al 2007;Scruton et al 2005). Similarly, domestic rainbow trout in the South Fork American River (California USA), with SL [ 25 cm, were not forced downstream by daily pulsed flow increases from 5 to [40 m 3 s -1 .…”
Section: Downstream Displacementmentioning
confidence: 90%
“…In contrast, the longitudinal displacement of larger fish seems less likely due to their increased swimming performance, compared with smaller fishes (Webb 1971), unless there are velocity refugia that are more accessible to smaller-sized fish. Field studies have found no consistent effect of sudden, extreme peaking flows on area use or movements by adult trout and salmon (Bunt et al 1999;Gido et al 2000;Scruton et al 2005;Heggenes et al 2007). …”
Section: Introductionmentioning
confidence: 99%